THROUGH THE LENS OF STRIFE: PALESTINIAN AND ISRAELI CINEMA EXAMINING SEXUALITY AND NATIONALISM DURING THE AL-AQSA INTIFADA - Goldstein, Daniel Ethan; Levin, Miriam Sarah (Ayden Journal of Management and Social Sciences, 2024)
This analysis examines the portrayal of interracial same-sex relationships in Israeli and Palestinian cinema produced during the al-Aqsa Intifada (2000–2008), shedding light on the intricate interplay of post-trauma, nationalism, race, and sexuality. While gay cinema in Israel has a longstanding history, addressing interracial relationships among men since the 1980s, Palestinian cinema grapples with the complexities of self-definition, national identity, and spatial constraints, given its unique status as both national and stateless. This study reveals a divergence in the cinematic treatment of these themes, highlighting how Palestinian cinema, in its pursuit of redefining Palestinian space and constructing a national narrative, has yet to address issues of sexual identity and interracial intimacy within the narrative framework.